Islamic integrated exposure response therapy for mental pollution subtype of contamination obsessive-compulsive disorder: a case report and literature review. Issue 2 (7th February 2018) - Mohamad Arip, Ameerah Adeelah; Sharip, Shalisah; Md Rosli, Ahmad Nabil
ABSTRACT: Contamination obsession is the commonest subtype of obsessive-compulsive disorder (OCD), and has been found to be higher among Muslim populations. The presentation of clinical OCD is influenced by one's religious belief, practice, and culture. Islamic rituals that emphasise on cleanliness or ritual purity could explain why the common contents of obsessions/compulsions among Muslim population are contamination and religion. We want to examine whether Islamic Integrated exposure response therapy (IERT) is suitable for mental pollution. We report a 27-year-old Muslim lady with an acute onset of contamination OCD, complicated with secondary depression. Her fear of contamination was strongly related to impurity and pertaining to Islamic rituals. Ten sessions of IERT were conducted. The patient improved clinically and objectively following the IERT. IERT is another variant of treatment mode that can be used to treat OCD, especially with contamination themes.